Idiosyncratic Characteristics of Postural Sway in Normal and Perturbed Standing - Sakanaka, Tania E.; Lakie, Martin; Reynolds, Raymond F. (Frontiers in Human Neuroscience, 2021)
OBJECTIVE Are people with a characteristically large physiological sway rendered particularly unstable when standing on a moving surface? Is postural sway in standing individuals idiosyncratic? In this study, we examine postural sway in individuals standing normally, and when subtle continuous sinusoidal disturbances are applied to their support platform. We calculate consistency between conditions to verify if sway can be considered characteristic of each individual. We also correlate two different aspects of participants’ responses to disturbance; their sway velocity and their regulation of body orientation. METHODS Nineteen healthy adults (age 29.2 ± 3.2 years) stood freely on footplates coaxially aligned with their ankles and attached to a motorized platform. They had their eyes closed, and hips and knees locked with a light wooden board attached to their body. Participants either stood quietly on a fixed platform or on a slowly tilting platform (0.1 Hz sinusoid; 0.2 & 0.4 deg). Postural sway size was separated into two entities: (1) the spontaneous sway velocity component (natural random relatively rapid postural adjustments, RMS body angular velocity), and (2) the evoked tilt gain component (much slower 0.1 Hz synchronous tilt induced by the movement of the platform, measured as p-p gain, ratio of body angle to applied footplate rotation). RESULTS There was no correlation between the velocity of an individual’s sway and their evoked tilt gain (r=0.34, p=0.15 and r=0.30, p=0.22). However, when considered separately, each of the two measurements showed fair to good absolute agreement within conditions. Spontaneous sway velocity consistently increased as participants were subjected to increasing disturbance. Participants who swayed more (or less) did so across all conditions (ICC(3,k) = 0.95). Evoked tilt gain also showed consistency between conditions (ICC(3,k) = 0.79), but decreased from least to most disturbed conditions. CONCLUSION The two measurements remain consistent between conditions. Consistency between conditions of two very distinct unrelated measurements reflects the idiosyncratic nature of postural sway. However, sway velocity and tilt gain are not related, which supports the idea that the short-term regulation of stability and the longer-term regulation of orientation are controlled by different processes.